Fundamentos praticados por uma equipe feminina de voleibol sub 15 durante o campeonato paranaense de 2015 - Kautzner Marques Junior, Nelson (Educación Física y Ciencia.)
The objective of the study was of quantify the skills practiced according the position of the volleyball player and the game system of a female team under 15 during the competition. The 19 games of the Paraná championship of 2015 were filmed and were later analyzed with a scout elaborate in the Excel® 2013. Kruskal Wallis Anova detected significant difference (p≤0,05) of the pass and of the attack of the middle player, in the set and in the defense of the setter. The Mann Whitney U test detected significant difference (p≤0,05) in the pass in relation to the game system in all the sets. In conclusion, the study on the number of skills practiced by a young team is relevant for the coach elaborate the load of the session